Comprehensive analysis of geometric hole designs and configurations in film cooling for gas turbine engines: a critical review - Abu Talib, Abd Rahim; Mohd Zulkeple, Muhammad Fitri; Harmin, Mohammad Yazdi; Saadon, Syamimi; Azami, Muhammad Hanafi; Yusaf, Talal (The Aeronautical and Astronautical Society of the Republic of China, 2024)
This paper provides a comprehensive review of the geometric design and configuration of film cooling holes. It highlights a critical concern in film cooling, which is the interaction between the main airflow and the cooling jet emerging from the holes. This interaction significantly influences various factors associated with hole design, including the length-to-diameter ratio (L/D), the exit-to-inlet cross-sectional area ratio (AR), the pitch-to-diameter ratio (P/D), and the compound angle of the hole. Furthermore, the paper discusses the introduction of flow disturbances, such as vortex generators, upstream of the cooling holes, as well as the construction of trenches around these holes. These modifications aim to alter the behaviour of the boundarylayer flow and its interaction with the film-cooling jet. The paper offers a comprehensive examination of these aspects, shedding light on the complex relationship between geometric design, flow modification, and film cooling effectiveness. Over time, hole design has evolved from cylindrical shapes to more complex designs, which improved cooling. Longer holes (L/D > 3) perform better in film cooling than short holes (L/D ≤ 3) due to fully developed coolant flow. The aspect ratio and pitch affect coolant distribution, and compound angled holes improve lateral coverage. According to the literature covered in this study, film cooling has progressed in several design characteristics. However, the adjustments made are not an instant fix for this method defects. Future research should develop unique approaches and optimizations to solve film cooling's problems and complexities.